FINANCIAL ASSISTANCE FOR THE SUBSCRIPTION OF SECURITIES: A COMPARISON OF SECTION 38 OF THE COMPANIES ACT 61 OF 1973 AND SECTION 4 OF THE COMPANIES ACT 71 OF 2008 - Tshegofatso Kgarabjang (Obiter, 2014)
Section 38 of the Companies Act 61 of 1973 prohibited a company to provide financial assistance for the acquisition of shares not only in the company itself or its holding company but also subsidiary. The legislature, when amending section 38, through the Companies Amendment Act 37 of 1999 failed to remove the prohibition in section 38, only incorporating solvency and liquidity test. Section 44 of the new Companies Act 71 of 2008 permits a company to provide financial assistance for the acquisition of or subscription of company’s securities, not only in the holding company but also in the subsidiary (or related company). The aim of this article is to compare section 38 of the old Act and section 44 of the new Act and highlight changes made by the section 44.